Lead exposure in Nunavik: from research to action - Ariane Couture; Benoît Levesque; Éric Dewailly; Gina Muckle; Serge Déry; Jean-François Proulx (International Journal of Circumpolar Health, 2012)
Background. In 1999, the Government of Canada regulated the use of lead shot for hunting. Concurrently, the Nunavik Regional Board of Health and Social Services (NRBHSS) was informed of the results of an isotope study that pointed to lead ammunition as a likely source of lead exposure in Nunavik. Rapidly thereafter, a coalition for the banning of lead shot was implemented by the NRBHSS as well as by regional/local partners and by Inuit hunters in order to disseminate this information to the public. Objectives. The purpose of this article is to describe the intervention conducted in the winter of 1999 by the NRBHSS and to assess the combined impact of national legislation and an awareness campaign on blood lead levels in Nunavik. Study design. Impact assessment of the intervention for the banning of lead shot conducted in 1999 in Nunavik using blood lead levels data before and after the intervention. Methods. Data on blood lead levels in Nunavik describing foetal exposure as well as during childhood and in adults published between 1992 and 2009 were compiled. Blood lead levels in Nunavik prior to and after the interventions were compared. To assess the current situation, the most recent blood lead levels were compared with those from surveys conducted during the same period in North America. Results. Analysis of blood samples collected from umbilical cord and from adults show that blood lead levels in Nunavik significantly declined between 1992 and 2004. Nevertheless, lead exposure in Nunavik still remains higher in comparison to that observed in other North American surveys. Conclusions. The current situation regarding lead exposure in Nunavik has significantly improved as a result of the implemented intervention. However, according to recent data, a gap still subsists relative to other North American populations.